Changes in Craniovertebral Angle and Sagittal Shoulder Angle: Comparation between Modified Backpack and Conventional Backpack Users in 11- 12 Aged Boys - Theresia D Arini Leman; Ferial H Idris; I Nyoman Murdana (Indonesian Journal of Physical Medicine & Rehabilitation, 2013)
Objectives: to develop a better design of ergonomic backpack and to evaluate the effect of wearing conventional and modified backpack on CVA and SSA changes.Methods: 34 male students of grade 5 and 6 elementary school who met the inclusion criteria (boys, 11-12 years old, normoweight, normoposture, and able to follow instruction) were included in theexperimental and cross sectional studies to evaluate duration, time of complaint, and changes in CVA and SSA between the conventional and modified backpack groups; and subject preference to backpackdesign. This study was statistically analysed through Mann-Whitneym Wilcoxon, and Mc Nemar tests.Results: The modified backpack with two compartments, hip strap, compartment strap and wide shoulder strap gives more benefits. Majority of students preferred the modified design to conventionaldesign. The modified design also gave students the ability to stand up longer. Narrowing CVA while wearing backpack was evident in conventional group (n=25) in comparison with modified group (n=15,p= 0.022). Moreover, narrowing SSA was also found more (n=18) in the conventional group than the modified group (n=4, p=0.000).Conclusions: Modified backpack design with two compartments, hip straps, wide shoulder straps, and compartment straps provides less CVA and SSA changes in comparison to conventional beckpackgroup. Minimal changes of CVA and SSA contributes to the development of a more ergonomic model of modified backpack to maintain postural stability.Key Words: posture, craniovertebral angle, backpack, ergonomics.